Funny girl: exploring the impact of learning and teaching humour in English Language GCSE - Lord, R (2024)
It is known that girls’ confidence declines during secondary school. Meanwhile, using humour in writing and speech has been shown to enhance persuasive skills and create confident speakers; the ability to use humour has been linked to progression in the workplace for women. However, there has been little research into the effect on teenage girls learning to use humour in the English classroom. This study examines which factors appear to prevent girls from using humour and whether particular teaching strategies might encourage it. The question of whether learning humour can aid academic risk-taking in the English classroom is also investigated. Surveys, semi-structured interviews with teachers and pupils, and the creation and testing of teaching interventions are employed in the investigation. Findings suggest that using simplified tasks and exemplars can successfully encourage girls to use humour. Additionally, there appears to be a range of reasons that may prevent this, such as lack of both confidence and preparation time. The willingness to take academic risks in the classroom transpires to be highly significant, especially with a Year 10 girls-only cohort when social anxiety is at peak levels. The small-scale study concludes that encouraging girls to use humour in their English Language GCSE could improve their ability to produce sophisticated persuasive content, and promote confidence. This can be achieved by allowing girls to experiment and iterate, providing multiple opportunities to use humour in English across their school career.